Les éditions de la Collectio sermonum d’Eusèbe d’Alexandrie - Gounelle, Rémi (Analecta Bollandiana, 2009)
In analyzing the research carried out by Augusti, Thilo and Mai, the author of the present article shows how the collection of Eusebius’ sermons came into being and explains the various oddities of the edition in Migne’s Patrologia graeco-latina.